Is there any relationship between monetary policy tools and external credit-growth nexus in Nigeria? - Oluwasogo S. Adediran; Emmanuel O. George; Philip Alege; Barnabas O. Obasaju (Cogent Economics & Finance, 2019)
The Nigerian economy attracts abundance of foreign capital inflows and credit supply; hence, an adverse external credit shock might lead to a large decrease of external inflows due to global credit tightening, which may leave the domestic economy in deep recession. In this case, domestic monetary policy tools should be preferred to mitigate the external adverse effect on the domestic economy and stimulate investment. As a result, an important issue of concern in this study is how can the use of monetary policy tools mitigate the effect of external credit shocks on economic growth in Nigeria? In answering this question, this study attempted to assess the influence of monetary policy tools on external credit and economic growth nexus in Nigeria, using annual data covering 36 years for the period 1980-2015. The study adopted the Cobb-Douglas production function and estimated a specified model using autoregressive distributed lag cointegration approach. The study found out that cash reserve requirement, which is credit policy easing, is significant in growing the Nigerian economy, as compared to monetary policy rate. The implication of this is that, if credit policy easing is properly implemented, it could be efficient in offsetting adverse external credit shocks.
Keywords: 330; Monetary policy; economic growth; capital inflows; credit supply and autoregressive distributed lag (ARDL)